Taxonomic notes on Agapetes (Ericaceae) from Xizang, China: Agapetes leiocarpa, a new synonym of A. atrosanguinea, and an updated description of A. camelliifolia - Yang, Bin; Wang, Ping-Yuan; Tong, Yi-Hua; Tan, Yun-Hong (Phytotaxa, 2021)
Based on field investigations and a review of relevant literature and specimens, Agapetes leiocarpa is shown to be conspecific with A. atrosanguinea and thus is reduced as a synonym under the latter. The floral morphology of A. camelliifolia is described for the first time based on living collections from the wild. Revised descriptions, color plates and taxonomic notes of these two species are also provided.